Phyto-Pathogenic Fungi Associated with Damping-off of Tomato in Himachal Pradesh - Bhardwaj, Swadha; Gupta, Meenu (International Journal of Economic Plants, 2023)
This study aims at identifying the major soil borne pathogens of tomato associated with damping-off in nursery areas. To achieve this, tomato nurseries of plant pathology farm of our area has been investigated. Samples with damping-off symptoms were collected and cultured under aseptic conditions. Fungi were isolated from diseased stem and roots on potato dextrose agar (PDA) medium. Growing colonies of fungi were purified by single spore and hyphal tip methods. Based on the morphological characters and pathogenicity tests, fungal species were identified as Pythium ultimum, Fusarium oxysporum, Rhizoctonia solani and Sclerotium rolfsii.